Preparação, caracterização e aplicação de um material catalisador para os processos fenton heterogêneo e fotocatálise heterogênea - Fabrício Vieira de Andrade (2010)
In this work it was prepared a catalytic system using Fe(III) ions supported on an autoclaved cellular concrete. After characterization by X-ray powder diffraction (DRX), 57Fe-Mössbauer spectroscopy, Thermogravimetric analysis (TG), Surface Area Measurements (BET), Atomic Absorption Spectrometry, Scanning Electron Microscopy (SEM) and Density Measurements, a catalytic investigation was performed. This study has been focused on the degradation, by Fenton or heterogeneous Photocatalysis, of dyes employed in industrial process. Since the catalytic system is less dense than water it remains on the surface of effluents or wastewaters. Hence it can be easily removed after finishing the treatment process. The concrete possess traces of hematite in its structure, which originates from its components. The gap of energy of this material is low enough to allow the activation of the photocatalytic process by solar energy. The prepared system was employed in the degradation, by Fenton and heterogeneous Photocatalysis, of Indigo Carmine used in textile industry. The process was monitored by ultraviolet spectroscopy in the visible region and the generated products were identified by mass spectrometry ionization eletronspray (ESI-MS/MS). The degree of mineralization of the dye in both processes was monitored by analysis of Total Organic Carbon (TOC). The toxicity of generated products, for both processes, were tested in cells Verona (monkey kidney cell), which is a standard test for toxicity in mammals, and brine shrimp, which is a very important environmental probe.